2022
DOI: 10.1002/app.53366
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of laponite: An effective approach to improve the mechanical properties and thermostability of collagen hydrogel

Abstract: Rapid aggregate precipitation of collagen and laponite in solution restricted the development of corresponding hybrid materials. Herein, a facile method of immerging collagen hydrogel into laponite dispersion was adopted to prepare hybrid collagen/laponite hydrogel, avoiding the precipitation. Collagen hydrogel shrunk and water content decreased dramatically after laponite solution treatment. According to the images of Scanning electron microscopy and energy dispersive system, the uniformly dispersed laponite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…As shown in Fig. 1c, the FTIR spectra of Lap as well as Eu(DPA) 3 @Lap show the signals centered at 3436 and 1007 cm −1 , which could be assigned to the -OH bending vibration and -Si-Ostretching vibration, respectively, 21 demonstrating the presence of Lap in our material. The FTIR spectrum of Eu(DPA) 3 @Lap lacks the characteristic absorbance of DPA at 1700 cm −1 , which is attributed to the -COOH group stretching vibration, indicating the successful coordination between the -COOH group and Eu.…”
Section: Resultsmentioning
confidence: 66%
“…As shown in Fig. 1c, the FTIR spectra of Lap as well as Eu(DPA) 3 @Lap show the signals centered at 3436 and 1007 cm −1 , which could be assigned to the -OH bending vibration and -Si-Ostretching vibration, respectively, 21 demonstrating the presence of Lap in our material. The FTIR spectrum of Eu(DPA) 3 @Lap lacks the characteristic absorbance of DPA at 1700 cm −1 , which is attributed to the -COOH group stretching vibration, indicating the successful coordination between the -COOH group and Eu.…”
Section: Resultsmentioning
confidence: 66%
“…In agreement with our results, Li et al showed the enhancement of mechanical properties of a 5 mg/mL cattle skin collagen hydrogel at different Laponite concentration addition. They showed that the elastic modulus, fracture stress, compression modulus, and rupture point of hydrogel treated by 10% LapNC were 695.2 Pa, 253.3 kPa, 13.5 kPa, and 76.7%, respectively, which were about 3.5, 5.5, 45.0, and 1.4 times larger than those of regular collagen-based hydrogel …”
Section: Resultsmentioning
confidence: 99%
“…They showed that the elastic modulus, fracture stress, compression modulus, and rupture point of hydrogel treated by 10% LapNC were 695.2 Pa, 253.3 kPa, 13.5 kPa, and 76.7%, respectively, which were about 3.5, 5.5, 45.0, and 1.4 times larger than those of regular collagen-based hydrogel. 36 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Becher et al showed IC50 values of approximately 0.5–1.5 mg/mL Laponite when incubated with HeLa or MCF-7 cells [ 88 ]. Li et al reported Laponite concentrations of up to 10% w / v (100 mg/mL) showed insignificant changes in the cellular viability of pre-osteoblastic MC3T3-E1 cells [ 89 ]. Therefore, the range of IC50 values of Laponite varies rather considerably.…”
Section: Degradation and Cytotoxicity Of Laponitementioning
confidence: 99%